EVALUASI KELEMBAGAAN PERANGKAT DAERAH KABUPATEN SUMEDANG - Jona Bungaran Basuki Sinaga (Jurnal Pemerintahan Dan Keamanan Publik (JP dan KP), 2019)
This study aims to analyze the condition of the existing regional equipment of the Sumedang Regency government. The population of this evaluation activity is all regional apparatus organizations in Sumedang Regency. Respondents in this evaluation are the Team assigned by each government agency in accordance with the level of the organization. The evaluation results show that most organizations are in the composite rating category P4. That is, in terms of structure and process, the organization is considered to be classified as effective, able to accommodate the organization’s internal needs and be able to adapt to the dynamics of changes in the organization’s external environment. However, the structure and process of the organization still has several minor weaknesses that can be addressed immediately if improvements are made through routine actions that are marginal. The SKPD in Sumedang District has met the organizational standardsset by the central government, although in some aspects such as the use of information technology and also the openness of data access in each organization has not been implemented to the full. Keywords: Institutional Evaluation; Organizational structure; Organizational Process